Metrics to assess the quantity of antibiotic use in the outpatient setting: a systematic review followed by an international multidisciplinary consensus procedure. (6th June 2018) - Versporten, Ann; Gyssens, Inge C; Pulcini, Céline; Monnier, Annelie A; Schouten, Jeroen; Milanič, Romina; Stanić Benić, Mirjana; Tebano, Gianpiero; Le Maréchal, Marion; Zanichelli, Veronica; Huttner, Benedikt; Vlahović-Palčevski, Vera; et al.
Abstract: Background: The international Innovative Medicines Initiative (IMI) project DRIVE-AB (Driving Reinvestment in Research and Development and Responsible Antibiotic Use) aims to develop a global definition of 'responsible' antibiotic use. Objectives: To identify consensually validated quantity metrics for antibiotic use in the outpatient setting. Methods: First, outpatient quantity metrics (OQMs) were identified by a systematic search of literature and web sites published until 12 December 2014. Identified OQMs were evaluated by a multidisciplinary, international stakeholder panel using a RAND-modified Delphi procedure. Two online questionnaires and a face-to-face meeting between them were conducted to assess OQM relevance for measuring the quantity of antibiotic use on a nine-point Likert scale, to add comments or to propose new metrics. Results: A total of 597 articles were screened, 177 studies met criteria for full-text screening and 138 were finally included. Twenty different OQMs were identified and appraised by 23 stakeholders. During the first survey, 14 OQMs were excluded and 6 qualified for discussion. During the face-to-face meeting, 10 stakeholders retained five OQMs and suggestions were made considering context and combination of metrics. The final set of metrics included defined daily doses, treatments/courses and prescriptions per defined population, treatments/courses and prescriptions per defined number of physician contacts and seasonal variation of total antibiotic use. Conclusions: A small set of consensually validated metrics to assess the quantity of antibiotic use in the outpatient setting was obtained, enabling (inter)national comparisons. The OQMs will help build a global conceptual framework for responsible antibiotic use.